Ponjatija «anklav / jenklav» i «jeksklav» i ih ispol'zovanie dlja politiko-geograficheskoj harakteristiki Kaliningradskoj oblasti [The concepts of enclave and exclave and their use in the political and geographical characteristic of the Kaliningrad region] - Rozhkov-Yuryevsky Yuri (Балтийский регион, 2013)
This article focuses on the genesis of and correlation between the related concepts of enclave and exclave and the scope of their use in different sciences, fields of knowledge, and everyday speech. The author examines the circumstances of their emergence in the reference and professional literature in the Russian language. Special attention is paid to the typology of the world’s enclave territories as objects of political geography; at the same time, their new categories and divisions (international enclave, overseas exclaves, internal enclaves of different levels) are extended and introduced. The author offers a new classification of contemporary and historical enclaves and exclaves. The article identifies the specific features of the Kaliningrad region in comparison to other enclave territories. The difference between the exclavity of the Kaliningrad region in the Soviet and post-Soviet periods is emphasised. The author shows the evolution of the use of concepts of enclave and exclave for describing the fe atures of the Kaliningrad region’s positions from the perspective of the mother and surrounding states. The article introduces the concept of dividing states and stresses the need to take their interests into account to ensure the functioning of the Russian exclave. The author substantiates the thesis that the Russian region is an enclave of the European Union (but not NATO) and an exclave of the Russian Federation and a number of political and economic intergovernmental alliances with Russian participation. The article offers a generalised characteristic of the Kaliningrad region from the perspective of its enclavity / exclavity.